Comparison of earthquake monitoring capability of the Ningxia network before and after completion of the early warning project - Hao Tang; Xuebo Li; Jinyin Xu; Qiuju He; Ziqi Hu (地震科学进展)
Post the completion of the Ningxia sub-project of the National Earthquake Intensity Quick Report and Early Warning Project, the number and distribution of stations in the Ningxia network have changed greatly. Using the background noise level method, the seismic monitoring capability of the Ningxia network was evaluated and compared before and after completion of the early warning project. Based on the positioning of three units, completion of the early warning project increased the average value of earthquake monitoring capacity in the Ningxia region to ML1.1, with a minimum value was ML0.5. This level is 0.5 higher than that before the completion of the project. Of the region’s seismic monitoring capabilities, 95% have a minimum magnitude of ML1.3. After the completion of the project, the average seismic monitoring capability of Ningxia and its surrounding areas (34.5°N～40.5° N, 103.5°E～108.5° E) was ML1.2, and the minimum value was ML0.3. This level is 0.7 higher than that before the completion of the project. Of the region’s seismic monitoring capacity, 95% has a minimum magnitude of ML1.6. Considering the positioning of 4, 5 and 6 units, the average seismic monitoring capacity of Ningxia region increased to ML1.2, ML1.3 and ML1.4, respectively. These levels are also 0.5 higher than before the construction of the early warning project. The average seismic monitoring capacity of Ningxia and its surrounding areas reached ML1.4, ML1.5 and ML1.6, respectively, which is 0.6 degree higher than the average monitoring capacity before the completion of the project. Therefore, the early warning project has greatly improved the earthquake monitoring capability in Ningxia and its surrounding areas.